2021
DOI: 10.1051/bioconf/20213800062
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical diversity of Spiraea hypericifolia (Rosaceae) growing under natural conditions in Novosibirsk Oblast

Abstract: A study on some morphological characteristics and the set and levels of phenolic compounds was performed for the first time on Spiraea hypericifolia L. (Rosaceae Juss.) growing under natural conditions in the Novosibirsk region (four sites). Two phenotypic varieties of S. hypericifolia were identified. Twenty-three phenolic compounds were found in aqueous-ethanol extracts from S. hypericifolia leaves by high-performance liquid chromatography. Chlorogenic, p-hydroxybenzoic, and p-coumaric acids and quercetin, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…A literature review of the chemical composition of Spiraea species also showed that the majority (over 25) of flavonoid compounds are quercetin and its derivatives [ 25 ]. During an investigation of the chemical composition of some Spiraea species, we attempted to study phenolic components of Spiraea representatives from Asian Russia, including Spiraea hypericifolia L. [ 26 , 27 ]. Data on other chemical components of S. hypericifolia L. are fragmentary; the plant has been found to contain such compounds as flavonols, proanthocyanidins, and catechins [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review of the chemical composition of Spiraea species also showed that the majority (over 25) of flavonoid compounds are quercetin and its derivatives [ 25 ]. During an investigation of the chemical composition of some Spiraea species, we attempted to study phenolic components of Spiraea representatives from Asian Russia, including Spiraea hypericifolia L. [ 26 , 27 ]. Data on other chemical components of S. hypericifolia L. are fragmentary; the plant has been found to contain such compounds as flavonols, proanthocyanidins, and catechins [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of metabolites in the retention time interval from 1 to 9 min helped us to identify compounds that are amino acids and sugars, as well as several phenolic compounds. Among the amino acids, the presence of L-lysine (1), L-tyrosine (2), proline (3), asparagine (5), and L-glutamic acid (4) was noted. From the class of sugars (retention time 1.65 min), α-lactose was identified (6).…”
Section: Resultsmentioning
confidence: 99%
“…Species of the genus Spiraea, including S. hypericifolia, are ornamental plants and are often used to decorate gardens and parks [1]. Species of the genus Spiraea are known as valuable ornamental plants, and for some of these species, the biological activity of their extracts and individual compounds has been documented, including anti-inflammatory, antioxidant, antiviral, antibacterial, antifungal, anticancer, and other effects [4][5][6][7][8][9][10]. Spiraea hypericifolia is one of these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation